Identification of cytokine-induced modulation of microRNA expression and secretion as measured by a novel microRNA specific qPCR assay - Benes, Vladimir; Collier, Paul; Kordes, Claus; Stolte, Jens; Rausch, Tobias; Muckenthaler, Martina; Häussinger, Dieter; Castoldi, Mirco (Scientific reports, 2015)
microRNAs are an abundant class of small non-coding RNAs that control gene expression post-transcriptionally. Importantly, microRNA activity participates in the regulation of cellular processes and is a potentially valuable source of biomarkers in the diagnosis and prognosis of human diseases. Here we introduce miQPCR, an innovative method to quantify microRNAs expression by using Real-Time PCR. miQPCR exploits T4 RNA ligase activities to extend uniformly microRNAs’ 3′-ends by addition of a linker-adapter. The adapter is then used as ‘anchor’ to prime cDNA synthesis and throughout qPCR to amplify specifically target amplicons. miQPCR is an open, adaptable and cost-effective procedure, which offers the following advantages; i) universal elongation and reverse transcription of all microRNAs; ii) Tm-adjustment of microRNA-specific primers; iii) high sensitivity and specificity in discriminating among closely related sequences and; iv) suitable for the analysis of cellular and cell-free circulating microRNAs. Analysis of cellular and cell-free circulating microRNAs secreted by rat primary hepatocytes stimulated with cytokines and growth factors identifies for the first time a widespread modulation of both microRNAs expression and secretion. Altogether, our findings suggest that the pleiotropic activity of humoral factors on microRNAs may extensively affect liver function in response to injury and regeneration.
Gesehen am 20.05.2020